2018
DOI: 10.1021/acs.jpcc.8b01084
|View full text |Cite
|
Sign up to set email alerts
|

Competing Energy Transfer Pathways in a Five-Chromophore Perylene Array

Abstract: A perylene (donor−dimer)−acceptor− (donor−dimer) pentamer array is synthesized to investigate the competition between excimer formation and Forster resonance energy transfer. Using time-resolved fluorescence, we show that, upon excitation, the isolated perylene dimer forms an excimer with a time constant of 4.3 ns. However, in the pentamer array, when either of two constituent dimers donate their energy to the acceptor fluorophore, the excimer energy trap is eliminated. The pentamer macromolecule shows broad a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…A similar but less drastic trend is seen with the red PDI NPs ( Table S1 ). This is indicative of the H-aggregate behavior 36 —where the radiative transition moments of the aggregated molecules partially cancel each other, thus increasing the lifetime of spontaneous emission.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…A similar but less drastic trend is seen with the red PDI NPs ( Table S1 ). This is indicative of the H-aggregate behavior 36 —where the radiative transition moments of the aggregated molecules partially cancel each other, thus increasing the lifetime of spontaneous emission.…”
Section: Resultsmentioning
confidence: 93%
“… 32 34 The tendency of PDIs to form self-assembled aggregates mean that they are versatile chromophores for the construction of novel functional supermolecular assemblies. 34 36 By changing the functionality of both the imide and bay positions of the PDIs, various derivatives have been explored for applications in supramolecular assembly, liquid crystals, artificial light-harvesting systems, and organic photovoltaics. 37 , 38 Aggregation can be decreased by functionalizing the diimide end-groups with bulky substituents that impede cofacial π–π interactions between the PDIs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, researchers have attempted to create efficient light-harvesting antenna complexes. More recently, research studies have begun mimicking the energy cascade systems found in natural photon-driven structures. These systems aim to separate absorption and emission events via transferring energy from an accepter to an emitter through an energy-transfer process, such as the Förster resonance energy transfer (FRET). This has been achieved in both semiconductor heterostructured quantum dots and rods and organic dye systems. , We propose the creation of a hybrid organic/inorganic light-harvesting complex via the attachment of organic chromophore ligands to a semiconductor nanocrystal.…”
Section: Introductionmentioning
confidence: 99%
“…Luminescence of both free (F) and self-trapped (ST) excitons (henceforth they will be designated as dimeric excitons) have been observed in both α-pyrene and α-perylene crystals at low temperature (say, below 50 K). In these crystals at room temperature, delocalized free excitons generated by photoexcitation are rapidly relaxed into ST excitons because of strong exciton–phonon interaction. , ST excitons are considered as excimers, which emit spectrally red-shifted, broadened excimer luminescence, which is a forbidden transition. A two-step excimer formation mechanism has been proposed from the results of temperature-dependent fluorescence studies as well as ultrafast dynamics studies. ,, However, only a few of these studies reported migration dynamics of excitons in these crystals, probably because of rapid relaxation of free excitons into excimers (within a few ps), which prevents excitons from being propagated even over a few nanometers. ,,,, In contrast to the concept that molecular excimers are trapped states and hence should be immobile, Pensack et al revealed that the excimer was diffusive and considered as a singlet exciton. ,, However, it is now well understood that diffusivity of the dimeric excitons is much slower than that of the monomeric excitons because the resonance energy transfer process involving ST excitons must be accompanied by intermolecular structural changes that can cause the diffusion process to be thermally activated. ,,,, On the other hand, the monomeric excitons populated in the β-form of the crystals have larger mobility. ,, …”
Section: Introductionmentioning
confidence: 99%